Passive fault-tolerant scheme of a 2 × 3-phase spmsm driven by mono-inverter based on field oriented control - Zhu, Xuhui (2024)
Fault-tolerant control (FTC) strategy can be realized without modifying the peripheral hardware circuit when the open-circuit fault (OCF) occurs in the multiphase motor. However, FTC relies on accurately identifying the fault location and switching to a new reconfiguration fault-tolerant algorithm. This can significantly increase the complexity of the system. To overcome the challenge, this article investigates a passive fault-tolerant scheme of a 2 × 3-phase surface-mounted permanent-magnet synchronous motor (SPMSM) driven by a mono-inverter when single-phase OCF occurs. The state equations based on field-oriented control of 2 × 3-phase SPMSM under healthy and single-phase OCF are discussed. The special motor drive mode and the constraint of id = 0 make the phase currents of each module passively optimized under the two neutral point configurations (i.e., isolated or connected), thus meeting the demand of restraining torque ripple. In the proposed PFTS, when the OCF occurs, the system does not require to attempt to diagnose or correct faults. Hence, a seamless transition from normal to faulty operation is guaranteed. Moreover, it enhances system reliability and stability. Furthermore, taking an existing 2 × 3-phase SPMSM as an example, the experiments are carried out for validation.